PERBEDAAN KUALITAS HIDUP PASCA INFEKSI COVID-19 PADA WANITA YANG BERISIKO TINGGI DENGAN WANITA YANG BERISIKO RENDAH TERINFEKSI SARS-CoV-2 - Camila, Rifdah; Dora Samaria (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The infection of SARS-CoV-2 holds the potential to impact an individual's quality of life. While previous research has delved into its effects, studies specifically pinpointing disparities in post-COVID-19 infection quality of life, particularly among high-risk (WBT) and low-risk (WBR) women, remain scarce. This study aims to elucidate the quality of life of women post-COVID-19 infection in the WBT and WBR cohorts at the Kebagusan Community Health Center, South Jakarta. Methods Employing a cross-sectional design, 206 participants were allocated into 103 WBT and 103 WBR groups utilizing a proportional random sampling method. Data collection entailed the utilization of the Ferrans Generic Version questionnaire and the Power Quality of Life Index (QLI). Results analysis via the Mann-Whitney test exhibited noteworthy distinctions in quality of life, particularly in psychological/spiritual facets (p-value=0.034). Nonetheless, no significant differences were discerned in the domains of health and function (p-value=0.352), social and economic aspects (p-value=0.252), and familial relations (p-value=0.549). Variations in quality of life between WBT and WBR cohorts, notably in the psychological/spiritual dimension, post-COVID-19 infection were evidenced. It is suggested to employ a quasi-experimental design for future research endeavors aimed at assessing interventions geared towards enhancing the psychological/spiritual welfare of respondents.